Sintesis dan Karakterisasi Zeolit dari Abu Bagasse Sebagai Adsorben Logam Berat Cu(II) - Setiawan, Adhi; Hanun, Jihan Nabillah; Afiuddin, Ahmad Erlan (Universitas Diponegoro, 2020)
The relatively high silica content in bagasse ash can be used as raw material for making zeolite. Zeolite can be used as a heavy metal adsorbent in industrial wastewater treatment. This study aims to synthesize zeolite from bagasse ash and to apply zeolite as an adsorbent of Cu(II) in a continuous system reactor. The effects of contact time, zeolite size, and concentration of Cu(II) solution on the removal efficiency of metals have been studied in this research. The synthesis of zeolite was carried out using the hydrothermal method at 100Â°C for 7 hours. The synthesized zeolite was characterized using SEM-EDX, XRD, FTIR, and BET The adsorption process was carried out using a continuous reactor with a flow rate of 0.4 L/min and flowed for 60 minutes with sampling at 15-minute intervals. The zeolite size used was 100 and 200 mesh. The results of SEM-EDX analysis showed that Zeolite has an irregular morphology and contains Si at 35.15%. The XRD results show that the zeolite crystallinity is relatively low. The specific surface area of zeolite at size 100 mesh and 200 mesh were 439.48 m2 /g and 697.76 m2/g respectively. The best Cu(II) waste adsorption test results were obtained under zeolite conditions with a particle size of 200Â mesh, the concentration of Cu(II) wastewater of 25 mg/L, and an operational time of 60 minutes with a removal efficiency of Cu(II) of 41.57%